PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA PENDEKATAN SCIENTIFIC PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN UNTUK MELATIHKAN LIFE SKILLS SISWA SMP DAN MENINGKATKAN HASIL BELAJAR - Khairiyah, Ummu; Kirana, Tjandra; Widodo, Wahono (Universitas Negeri Surabaya, 2016)
A develop research was done about science learning materials (lesson plans, student’s worksheets, student’s book, and learning achivement test) Scientific approach to the 4D models to teach life skills and the aim of improving student learning outcomes. This research was trial to 35 of junior high school’s students of class VII academic year 2014/2015 with One-group pretest-posttest design. Analysis data is descriptive quantitative-qualitative and the results are Validity of learning material valid (3.50); Practicalitybased on: Readability of worksheets and teaching materials 86% students interesting and easy to understand; Feasibility of instruction good category (3.5); Students response of positive (97%); Effectiveness based on: Student activities are student center; student learning achivement increased (N-Gain: 0.75); Ability Life skills (Thinking skills, academic skills, social skills) have been trained and the result is increased. The conclusions of this research that science learning material with base Scientific approach to teach Life skills and and improve the student learning achivement in junior high school. Telah dilakukan penelitian dengan mengembangkan perangkat pembelajaran (RPP, LKS, Materi Ajar, Tes Hasil Belajar) dengan pendekatan Scientific model 4D yang bertujuan untuk melatihkan Life skills dan meningkatkan hasil belajar siswa SMP. Perangkat pembelajaran diujicoba pada 35 siswa kelas VII semester genap tahun ajaran 2014/ 2015 dengan rancangan uji coba One-Group Pretest-Posttest Design. Analisis data dilakukan secara deskriptif kuantitatif- kualitatif dengan hasil Validitas perangkat kategori valid(3,50), Kepraktisan perangkat yang meliputi: Keterbacaan LKS dan materi ajar siswa 86% menarik dan mudah dipahami; Keterlaksanaan pembelajaran sangat baik (3,5) ; Respon siswa positif (97%); Keefektifan perangkat pembelajaran yang meliputi: Aktivitas siswa bersifat student centered; Hasil belajar siswa meningkat (N-Gain: 0,75); Kemampuan Life skills (Thinking skills, academic skills, social skills) telah dilatihkan dan hasilnya meningkat. Simpulan penelitian ini, bahwa perangkat pembelajaran IPA dengan pendekatan Scientific layak untuk melatihkan life skills dan meningkatkan hasil belajar siswa SMP.